Effects of organic and inorganic additives on flotation recovery of washed cells of Saccharomyces cerevisiae resuspended in water - DeSousa, SR; Laluce, Cecília [UNESP]; Jafelicci, M. (Elsevier B.V., 2006)
Separation of microbial cells by flotation recovery is usually carried out in industrial reactors or wastewater treatment systems, which contain a complex mixture of microbial nutrients and excretion products. In the present study, the separation of yeast cells by flotation recovery was carried out using a simple flotation recovery systems containing washed yeast cells resuspended in water in order to elucidate the effects of additives (defined amounts of organic and inorganic acids, ethanol, surfactants and sodium chloride) on the cellular interactions at interfaces (cell/aqueous phase and cell/air bubble). When sodium chloride, organic acids (notably propionic, succinic and acetic acids) and organic surfactants (sodium dodecyl sulphate (SDS), cetyltrimethylammonium bromide (CTAB) and Nonidet P40) were added to the flotation recovery system, significant increases in the cell recovery of yeast hydrophobic cells (Saccharomyces cerevisiae, strain FLT-01) were observed. The association of ethanol to acetic acid solution (a minor by-product of alcoholic fermentation) in the flotation recovery system, containing washed cells of strain FLT-01 resuspended in water, leading to an increased flotation recovery at pH 5.5. Thus, the association among products of the cellular metabolism (e.g., ethanol and acetic acid) can improve yeast cell recovery by flotation recovery. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: froth flotation recovery; yeast; weak organic acid; sodium chloride; surfactants